Pengaruh E-Wom dan Brand Image terhadap Repurchase Intention pada Pengguna Aplikasi Dana - Susanto, Edy; Ahoen, Bahori; Handayani, Agustia (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2024)
Repurchase Intention can be interpreted as the intention to repurchase is a transaction made on a product or service that has been purchased and then makes a repeat purchase. The focus of the research, namely Repurchase Intention, is intended as a customer's decision to reuse the Dana e-wallet. The purpose of the study was to determine the influence of e-wom and brand image on Repurchase Intention on the Dana e-wallet application. The use of quantitative research methods with a sample of 72 respondents obtained from the reach of the questionnaire from Google Form. The data analysis technique is multiple linear regression with SPSS. In terms of percentage, E-WOM has a positive effect on Repurchase Intention. The more customers talk about the Dana application product, the more customers will use it repeatedly and eventually become a habit or even dependent because of its benefits and convenience. The conclusion of the study is that Brand Image has a positive effect on Repurchase Intention. The more famous and has a good brand image, the more customers will reuse the Dana application. A well-known brand will make customers comfortable and safe in using the Dana e-wallet. Suggestions for further research are that researchers can add Artificial Intelligence (AI) factors as research developments.